Progress and limitations in the content production of the Open-Circuit Television in Argentina - Retegui, Lorena (2022)
In this article we discuss the significant aspects of the current situation of the OpenCircuit Television in Argentina after three years of the enactment of the 26.522 Act. We focus especially on the minimal percentages of TV content production made by the channel owners that are required by the aforementioned Act. We also focus on the limit of retransmission chain that regulations determine which, along with the percentages of TV content production demanded, are the current issues to be addressed by the broadcasting entities outside the metropolitan area. The Act is enforced in a context of high concentrated audiovisual market and the strong influence of the Closed-Circuit TV. These issues show a challenge to the unprecedented role taken by the State in carrying forward a policy promoting the content production.